Alcohol consumption and health consequences among villagers in Thum Tong sub-district, Mueang Nan district, Nan province, Thailand - Thanawat Rattanawitoon (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2010